Indirect evidence for proton pump inhibitor failure in patients taking them independent of meals - Freigofas, Julia; Haefeli, Walter E.; Brenner, Hermann; Quinzler, Renate (Pharmacoepidemiology and drug safety, 2014)
Purpose: We investigated the association between conditions of proton pump inhibitor (PPI) treatment failure and food intake in an elderly ambulatory population. Methods: Our data originate from a large population-based cohort study. During a home visit done by a trained study physician, patients were asked for each medication to state whether it was taken in relation to a meal (before, concurrently with, and after) or independent of a meal. This information was analyzed for all patients taking a PPI daily and correlated to markers of PPI failure. Results: Out of 2717 patients participating in a home visit and taking at least one medication, 383 took a PPI daily (14.1%). A PPI intake independent of meals was defined as incorrect and was observed in 64 patients, whereas 319 patients took their PPI in relation to a meal, which was defined as the correct intake. Treatment failure was observed in 10 out of 64 (15.6%) PPI users with incorrect intake and in 18 out of 319 (5.6%) PPI users with correct intake. The risk of treatment failure was threefold higher in patients taking their PPI independent of meals (OR 3.35; 95%CI 1.44-7.76). Conclusion: The higher risk for PPI failure in patients taking PPIs independent of meals suggests that synchronized PPI administration with meals is indeed essential, and better counseling of patients is needed.